2015
DOI: 10.11646/zootaxa.4043.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of the Iranian Microgastrinae (Hymenoptera: Braconidae)

Abstract: In the present study, the Iranian Microgastrinae (Hymenoptera: Braconidae) fauna is summarized. It is based on a detailed study of all available published data and new material collected. In total 99 species belonging to 8 genera are from Iran: Apanteles Förster, 1862 (36 species), Cotesia Cameron, 1891 (34 species), Deuterixys Mason, 1981 (1 species), Diolcogaster Ashmead, 1900 (4 species), Microgaster Latreille, 1804 (4 species), Microplitis Förster, 1862 (11 species), Pholesetor Mason, 1981 (4 species) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…One of the largest braconid subfamily, Microgastrinae, is specialized on the parasitization of caterpillars (Shaw and Huddleston 1991). Both identified species of Cotesia Cameron ( C.spuria and C.zygaenarum ) are gregarious endoparasitoids of caterpillars (Žikić et al 2013; Gadallah et al 2015). Cotesiaspuria is a polyphagous and cosmopolitan species that inhabits whole Palaearctic (Yu et al 2012; Gadallah et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the largest braconid subfamily, Microgastrinae, is specialized on the parasitization of caterpillars (Shaw and Huddleston 1991). Both identified species of Cotesia Cameron ( C.spuria and C.zygaenarum ) are gregarious endoparasitoids of caterpillars (Žikić et al 2013; Gadallah et al 2015). Cotesiaspuria is a polyphagous and cosmopolitan species that inhabits whole Palaearctic (Yu et al 2012; Gadallah et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both identified species of Cotesia Cameron ( C.spuria and C.zygaenarum ) are gregarious endoparasitoids of caterpillars (Žikić et al 2013; Gadallah et al 2015). Cotesiaspuria is a polyphagous and cosmopolitan species that inhabits whole Palaearctic (Yu et al 2012; Gadallah et al 2015). During our study we identified C.spuria parasitizing caterpillars of D.caeruleocephala , which is recognized as a pest in orchards of the family Rosaceae (Bolu and Özgen 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the fauna of some subfamilies of the Iranian Braconidae have been catalogued (e.g., FARAHANI et al 2016), but the Microgastrinae have been poorly studied (FARAHANI et al 2014;GADALLAH et al 2015;GHAFOURI MOGHADDAM et al 2018;ABDOLI et al 2019a,b;ZARGAR et al 2019a,b). The objective of this study is to improve our knowledge of the Microgastrinae in Iran and the description of the fi rst Palaearctic Venanides identifi ed to the species level.…”
Section: Introductionmentioning
confidence: 99%
“…The Braconidae includes 21,221 described species worldwide classified into 45 subfamilies (Yu et al 2016) whžich are parasitoids of other insects (Wharton 1993). The fauna of Iranian Braconidae has been studied rather well and most of species have been catalogued earlier (e.g., Gadallah, Ghahari 2013a, 2013b, 2016Farahani et al 2014Farahani et al , 2016Gadallah et al 2015aGadallah et al , 2015bGadallah et al , 2016aGadallah et al , 2016bGhahari, 2016;Beyarslan et al 2017;Samin et al 2018;Sakenin et al 2018). Below new data on the Braconidae of the fauna of Iran is given.…”
Section: Introductionmentioning
confidence: 99%